Experimental Investigation on the Effect of Agitation and Flow Rate in Three-stage Continuous Stirrer Tank Reactors Connected in Series for Ethyl Acetate Saponification Reaction - Emiru Yidnekachew Melesse; Solomon Werkneh; Mulugeta Kebede Gebremeariam; Zelalem Belay Asrat; Dagne Abatie Gesese; Alemu Abdi (Challenges and Advances in Chemical Science Vol. 8, 2022)
A three-stage continuous stirrer tank reactor has been investigated for the ethyl acetate hydrolysis reaction. The reaction was tested using sodium hydroxide and ethyl acetate. The flow rate (40ml/min, 70 ml/min, and 100 ml/min), agitation rate (minimum, medium, and maximum), and temperature of non-isothermal conditions were all investigated for the saponification reaction. The results of nine tests were examined, with the initial concentrations of ethyl acetate and sodium hydroxide remaining constant throughout. The data was collected using NaOH (4%) and CH3COONA (6%) solutions. The minimum conductivity values, the maximum temperatures, and conversion values of the reaction were 45.2%, 66.34% at a temperature of 24.9°C for R1, 41.1%, 69.53% at a temperature of 24.5 for R2, and 40.7%, 69.76% at the temperature of 24ºC for R3 for 40 ml/min flowrate and minimum agitation rate individually. Based on the medium agitation rate and medium flow rate (70 ml/min), the minimum conductivity and maximum conversion values were 38.3% and 71.59%, respectively, at a temperature of 27.1°C of R1, 30.5% and 77.53 % at a temperature of 27.5°C of R2, and 27.8% and 79.59% at a temperature of 26.8°C of R3.Compared to others the reactions operated at a maximum flow rate (100 ml/min) and maximum agitation rate of the conductivity and conversion values were 43.1% and 67.94% of R1 at the temperature of 27.8ºC, 34.4% and 74.56% R2, 34.1% and 74.79% of R3 at the temperature of 28.3°C. The conductivity of the three-stage CSTRs connected in series decreased accelerably, but the conversion value increased progressively. The results of this evaluation may aid in the large-scale optimization of desired product production and predict the advantage of multiple-stage reactors connected in series that are particularly suitable for the saponification reaction of ethyl acetate.